Pneumonia – fatores de risco para mortalidade de pacientes internados em um hospital universitário - FERNANDES, Glaidineis Dias (2022)
Introduction: This study had the aim to evaluate mortality risk factors on patients with community-acquired pneumonia. Methods: A study with 56 inpatients having community acquired pneumonia and 32 patients having nosocomial pneumonia was carried out, the patients were admitted to a university hospital during the period from July 2004 through April 2005. Clinical, radiologic and laboratorial data were obtained and correlated with the patientes’ outcome (death or hospital discharge). The adopted significance level was 0,05. In addition, patients were classified according to the Fine score and CURP-65 score. Results: From the 56 studied community-acquired pneumonia patients. The following percentagens had death as outcome: 71% of those who had abnormal psychic features, 37% of those who had elevated respiratory rate; 60% of those who had increased serum creatinine levels and 60% of those who needed mechanical ventilation. All these data were statistically significant. The percentagem of patients that had pH levels lower than 7,35 and had death as outcome was significantly higher than of thoese who survived. In regard to nosocomial pneumonia the following percentagem had death as outcome: 70% of the patients who had pH levels lower than 7,35 and 78% of the patients who needed mechanical ventilation, both data were statistically significant. From the total of both community-acquired pneumonia and nosocomial pneumonia, 34 were classified as severy pneumonia (classes IV and V of Fine score), being 23 patients included on severity class IV and 11 patients on class V. From these patients, 17 (50%) died (7 patients with community-acquired pneumonia e 10 patients with nosocomial pneumonia). According to CURP-65 score, 29% patients were classified as having increased risk of mortality (2 to 5 scores), with 22 patients scoring 2; 4 patients scoring 3; 1 patient scoring 4 and 2 patient scoring 5. From these individuals, 13 (45%) had death as outcome (6 patients with community-acquired pneumonia and 7 with nosocomial pneumonia). Conclusion: Altered psychic status, abnormal respiratory rate, altered serum creatinine levels and the need for mechanical ventilation contributed as risk factores for mortality on community-acquired pneumonia patients, while pH levels lower than 7,35 and the need for mechanical ventilation influenced mortality of patients with nosocomial pneumonia. According to the Fine criteria, 34 from the total of patients were classified as having severy pneumonia, and 17 of those had death as outcome. When using CURP-65 score, 29 patients presented increased risk for mortality while 13 (45%) of the died.